Investigation and comparison of G6PD enzyme screening test costs for all newborns with treatment costs of patients with favism admitted due to hemolysis from 2014 to 2015 in Isfahan governmental hospitals - Sadinejad, Morteza; Motevalli Pour, Hamed; Yousefian, Saeed; Nik Khah, Roham (Medicinski časopis, 2021)
Introduction:The purpose of this study was to determine the costs of glucose-6-phosphate dehydrogenase (G6PD) deficiency screening tests in neonates and the cost of treatment for patients with favism who referred to the government hospitals of Isfahan with acute hemolysis and their comparison.Materials and methods:In this retrospective study, 116 patients with favism were selected, and their clinical data and treatment costs were recorded. Costs of neonatal G6PD screening tests were estimated based on quantitative and qualitative screening kits by referring to the laboratories of each hospital. The number of births in Isfahan province from October 2014 to October 2015 was 84760 individuals.Findings:Based on our results, 73 patients (62.9%) were males, and 43 of them (37.1%) were females. The causes for hemolysis were the consumption of broad beans in 78.4%, infection in 19.8% and drugs (Erythromycin and Keflin) in 1.7% of patients. The majority of patients (46.6%) received blood transfusion once, and 18.9% received 2 or more transfusions, while 34.5% had received no blood transfusions. The mean and standard deviation of patients' medical expenses were 7,472,005±7,329,847 Rials. The total cost of treatment for patients was 869,162,324 Rials. The screening cost for the whole newborns from October 2014 to October 2015 with qualitative kits was 754,364,000 Rials and with the qualitative kits was 960,330,800 Rials.Conclusion:The cost of the qualitative screening test for G6PD deficiency is lower than the costs of treatments of favism patients in Isfahan.